Beja Pedagogical Grammar - Wedekind, Klaus; Wedekind, Charlotte; Musa, Abuzeinab (AAeO - Afrikanistik-Aegyptologie-Online, 2008)
Primarily, this book is for students who want to know Beja. In addition, it contains useful information for linguists who want to know about Beja.